1875 Pa. Laws 33, No. 38, § 1 - (:unkn) unknown (My University, 1875)
Prohibited concealed carry of any firearms, slung-shots, billys, dirk-knives, razors, or any other deadly weapon with intent to maliciously do injury to any another person
Keywords: CARRY - INTENT TO COMMIT CRIME